Revitalizing Urban Governance: A Comprehensive Evaluation of E-Government in Padang City's Urban Villages through the Lens of the Five Pillars E-Government Framework - Rusnita, Widya Cancer; Aromatica, Desna; Putera, Roni Ekha (Universitas Teuku Umar, 2024)
The e-Kelurahan services program is one of the leading innovative programs in Padang City, which aims to realize the convenience of essential services at the urban village. The result of research in 2022 shows that the implementation of e-kelurahan has yet to be effective, and this study is a follow up research that aims to evaluate e-Kelurahan services using Maturity e-Government Models. The evaluation model used the Five pillars of e-Government framework put forward by Fietkiewicz, Mainka & Stock in 2017, which consists of Information Dissemination, Communication, Transactions, Interoperability, and Participation. The research method used qualitative descriptive through collecting data, interviews, observation, and documentation. According to the findings of the study, that four pillars must still be fulfilled. communication pillar through the website that is not presented to the public, the transaction pillar has decreased function because the community can no longer submit letters online, interoperability is not fulfilled because integration with Dukcapil is interrupted and the participation pillar of e-Kelurahan utilization is not used for more democratic things. The Government of Padang City has only reached the stage of providing online service applications to produce the documents. The weakness of this theory is that the analysis only focuses on website development, ignoring other factors such as organization, resources, and supervision, which are also implementation problems.